Organisational cultures and the evoked effects of leader ability on employee creativity. Issue 3 (9th October 2020) - Ogbeibu, Samuel; Senadjki, Abdelhak; Gaskin, James
Abstract : Purpose: This study seeks to investigate how leader ability and diverse organisational cultures (OC) act to influence employee creativity in manufacturing organisations. By leveraging the multifaceted nature of the competing values framework (CVF), this study examines the growing deterioration of employee creativity through the lens of four OC quadrants within the Nigerian manufacturing industry and further investigates how distinct OCs and leader ability can aid to bolster employee creativity. The CVF is a model used to assess organisational cultures, irrespective of their industry, for the overarching purpose of improving organisational performance. Design/methodology/approach: The target population consists of employees of research and development (R&D) and information technology (IT) in the headquarters of 21 manufacturing organisations. Our useable sample consisted of 439 responses from the Nigerian manufacturing industry. Findings: Results indicated that leader ability and adhocracy OC have positive effects on employee creativity. Market and clan OC have negative effects on employee creativity. Likewise, leader ability dampens the effects of adhocracy OC on employee creativity and reinforces the market OC effect on employee creativity. Originality/value: This study provides novel insights that challenges several controversial and contemporary postulations of extant research which theorise the OC–employee creativity relationships. By leveraging the construct of leader ability, unique contributions are also made to provoke congruence.